Human papillomavirus vaccine efficacy against invasive, HPV-positive cancers: population-based follow-up of a cluster-randomised trial - Joakim Dillner; Camilla Lagheden; Eero Pukkala; Tiina Eriksson; Tapio Luostarinen; Dan Apter; Matti Lehtinen; Katja Harjula; Marjo Kuortti; Johanna Palmroth; Tiina Petäjä; Pekka Nieminen; et al. (BMJ Open)
Background Human papillomavirus (HPV) vaccination protects against HPV, a necessary risk factor for cervical cancer. We now report results from population-based follow-up of randomised cohorts that vaccination provides HPV-type-specific protection against invasive cancer.Methods Individually and/or cluster randomised cohorts of HPV-vaccinated and non-vaccinated women were enrolled in 2002–2005. HPV vaccine cohorts comprised originally 16–17 year-old HPV 16/18-vaccinated PATRICIA (NCT00122681) and 012 trial (NCT00169494) participants (2465) and HPV6/11/16/18-vaccinated FUTURE II (NCT00092534) participants (866). Altogether, 3341 vaccines were followed by the Finnish Cancer Registry in the same way as 16 526 non-HPV-vaccinated controls. The control cohort stemmed from 15 665 originally 18–19 years-old women enrolled in 2003 (6499) or 2005 (9166) and 861 placebo recipients of the FUTURE II trial. The follow-up started 6 months after the clinical trials in 2007 and 2009 and ended in 2019. It was age aligned for the cohorts.Findings During a follow-up time of up to 11 years, we identified 17 HPV-positive invasive cancer cases (14 cervical cancers, 1 vaginal cancer, 1 vulvar cancer and 1 tongue cancer) in the non-HPV-vaccinated cohorts and no cases in the HPV-vaccinated cohorts. HPV typing of diagnostic tumour blocks found HPV16 in nine cervical cancer cases, HPV18, HPV33 and HPV52 each in two cases and HPV45 in one cervical cancer case. The vaginal, vulvar and tongue cancer cases were, respectively, positive for HPV16, HPV52/66 and HPV213. Intention-to-treat vaccine efficacy against all HPV-positive cancers was 100% (95% CI 2 to 100, p<0.05).Interpretation Vaccination is effective against invasive HPV-positive cancer.Trial registration number NCT00122681, Post-results; NCT00169494, Post-results; NCT00092534, Post-results.